PENGARUH PENGUNGKAPAN EMISI GAS RUMAH KACA TERHADAP NILAI PERUSAHAAN DENGAN STEM CEO SEBAGAI VARIABEL MODERASI - Tantri, Margaret Retno; Kusumaningtias, Rohmawati; Muthohhari, Abdullah Hanif (UNIKA Santo Thomas, 2025)
This article aims to analyze the effect of greenhouse gas (GHG) emissions disclosure on firm value in Indonesia's energy sector, considering the CEO's educational background in STEM as a moderating variable. The phenomenon that triggered this research is the increasing attention to the environmental impact of companies, especially in the energy sector which is the second largest contributor to emissions in Indonesia. The method used in this study is regression analysis with data from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange. The findings show that GHG emissions disclosure has a negative and significant relationship with firm value measured using Tobin's Q ratio. In addition, the CEO's STEM background does not show a significant moderating influence on the relationship. The implications of this study emphasize the importance of transparency in emissions disclosure and the need for more effective strategies in environmental management to increase firm value, as well as provide insights for decision makers within companies to consider STEM-based leadership in the management of environmental issues.